2013
DOI: 10.3844/ajassp.2013.515.524
|View full text |Cite
|
Sign up to set email alerts
|

Twist Springback Measurement of Autonomous Underwater Vehicle Propeller Blade Based on Profile Deviation

Abstract: Geometrical defects that are attributable to springback are among the major defects induced by the sheet metal forming process. Such defects are critical for sections with varying thickness, such as Autonomous Underwater Vehicle (AUV) propeller blades. In this study, the springback in the twist-bending of an AA6061 propeller blade was quantified by comparing the targeted and manufactured profiles obtained using the commercial threedimensional surface measurement technique. The results show that the twist sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The spring-back is recompensed through this punch uprooting. (Abdullah et al, 2013) have described that the spring-back in air twisting of metallic sheets are forecasted through the improved ANN. The spring-back and punch travel, pass on the hole to the section of bite the dust sweep proportion, two yields and strain solidifying type, punch range/thickness proportion and an edge of twist are the five sources of information in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The spring-back is recompensed through this punch uprooting. (Abdullah et al, 2013) have described that the spring-back in air twisting of metallic sheets are forecasted through the improved ANN. The spring-back and punch travel, pass on the hole to the section of bite the dust sweep proportion, two yields and strain solidifying type, punch range/thickness proportion and an edge of twist are the five sources of information in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…This can be concluded that the validation is reliable since the percentage difference are quite low for 2.2 mm thickness. From research by [12], the deviation below 10% is considered low in springback cases. For 3.2 mm thickness, the deviation is quite large because of the twisting moment goes beyond the plastic region of the section.…”
Section: Resultsmentioning
confidence: 99%
“…Focus variation, a technique mainly used for measuring geometrical defects such as surface waviness and roughness, gave 3D depth readings. As proposed by Abdullah et al [4], this method could also be used to evaluate geometric and dimensional defects of small propeller blades. Cavada and Fadón [5] gave a thorough assessment of various laser-based techniques for measuring marine propellers.…”
Section: Introductionmentioning
confidence: 99%